Pengaruh Kepemimpinan dan Motivasi Kerja terhadap Kinerja Pegawai Dinas Perumahan dan Kawasan Pemukiman Kabupaten Maybrat - Maryen, Andrei; Clan, Edward; Sasior, Agnes Aiterm (Innovative: Journal Of Social Science Research, 2025)
The purpose of this study was to analyze the influence of leadership and work motivation on the Performance of Employees of the Housing and Settlement Service of Maybrat Regency. The type of research used is quantitative with multiple linear regression analysis by conducting T tests, F tests, and determination coefficient tests. From the results of calculations using multiple linear regression analysis, the regression equation Y = 4.348 + 0.239X1 + 0.529X2 was obtained. Based on the results of the analysis and discussion, it was concluded that work motivation had a significant effect on the Performance of Employees of the Housing and Settlement Service of Maybrat Regency, while leadership did not affect performance, but simultaneously together work motivation had a significant effect on the performance of Employees of the Housing and Settlement Service of Maybrat Regency.